Avian Pox Infections in Southeastern Bobwhites: historical and Recent Information - William R. Davidson; Forest E. Kellogg; Gary L. Doster (National Quail Symposium Proceedings, 2017)
Historic and recent information on the occurrence of avian pox, an infectious viral disease, in southeastern bobwhite quail (Colinus virginianus) is summarized. An apparent long-term(> 50 year) low-level (< 2 percent) rate of infection occurred prior to an outbreak with a 12-fold increase in prevalence in 1978-1979. Post-outbreak monitoring during the two succeeding years disclosed that the regional prevalence of infection declined to near the pre-outbreak rate. The significance of avian pox as a regional and local mortality factor is discussed.